2019
DOI: 10.12688/f1000research.19997.2
|View full text |Cite
|
Sign up to set email alerts
|

The use of electron microscopy in the diagnosis of focal segmental glomerulosclerosis: are current pathological techniques missing important abnormalities in the glomerular basement membrane?

Abstract: Background: There is an increasing appreciation that variants of the COL4A genes may be associated with the development of focal segmental glomerulosclerosis (FSGS). On electron microscopy, such variants may produce characteristic changes within the glomerular basement membrane (GBM). These changes may be missed if glomerular lesions histologically diagnosed as FSGS on light microscopy are not subjected to electron microscopy. Methods: We conducted a retrospective cohort analysis of all patients presenting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The management of FSGS in LLMIC may face several limitations, even exceeding those faced by Priyanka et al A recent survey revealed that, while 88% of the pediatric nephrology centers in under-resourced areas have kidney pathology services available, the analysis of the biopsy is often restricted to just LM, which significantly limits its value for excluding several primary kidney diseases [6,16].…”
Section: Relevance and Generalizability To Other Under-resourced Regionsmentioning
confidence: 99%
“…The management of FSGS in LLMIC may face several limitations, even exceeding those faced by Priyanka et al A recent survey revealed that, while 88% of the pediatric nephrology centers in under-resourced areas have kidney pathology services available, the analysis of the biopsy is often restricted to just LM, which significantly limits its value for excluding several primary kidney diseases [6,16].…”
Section: Relevance and Generalizability To Other Under-resourced Regionsmentioning
confidence: 99%
“…The finding of a lamellated GBM is pathognomonic for a pathogenic COL4A5 or two COL4A3 or COL4A4 variants. However in individuals with FSGS a lamellated or thinned GBM is found less often because FSGS is often diagnosed on the basis of proteinuria without a kidney biopsy or where a kidney biopsy is performed, but the GBM was not examined, 26 .…”
Section: Focal and Segmental Glomerulosclerosismentioning
confidence: 99%